GENDER MAINSTREAMING AND WOMENS PARTICIPATION IN SACCO PROGRAMS IN SIRONKO DISTRICT. - AMUGE KAMULI DOREEN (My University, 2024)
The study investigated the effect of gender mainstreaming on women's participation in SACCO programs in Sironko District, focusing on cultural norms, beliefs, and strategies for improvement. Using a descriptive design with 63 participants, the findings showed that 67% of respondents identified cultural norms as barriers, limiting women’s involvement in SACCOs due to traditional roles. Additionally, 59% reported that cultural beliefs, such as views on financial independence, discouraged women’s participation. To improve inclusion, 70% suggested gender-sensitive policies, while 65% recommended community sensitization to challenge harmful beliefs. The study concludes that targeted interventions, including gender mainstreaming and educational programs, are essential to overcoming these barriers and promoting women’s economic empowerment in SACCOs.